Sex, aging and immunity in multiple sclerosis and experimental autoimmune encephalomyelitis: An intriguing interaction - Boziki, Marina; Theotokis, Paschalis; Kesidou, Evangelia; Karafoulidou, Eleni; Konstantinou, Chrystalla; Michailidou, Iliana; Bahar, Yasemin; Altintas, Ayse; Grigoriadis, Nikolaos (Frontiers in Neurology, 2023)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the Central Nervous System (CNS) with a profound neurodegenerative component early in the disease pathogenesis. Age is a factor with a well-described effect on the primary disease phenotype, namely, the relapsing-remitting vs. the primary progressive disease. Moreover, aging is a prominent factor contributing to the transition from Relapsing-Remitting MS (RRMS) to the secondary progressive disease. However, sex also seems to, at least in part, dictate disease phenotype and evolution, as evidenced in humans and in animal models of the disease. Recently, sex-specific gene expression profiles have elucidated an association with differential immunological signatures, in the context of experimental disease. This review aims to summarize current knowledge stemming from Experimental Autoimmune Encephalomyelitis (EAE) models regarding the effect of sex, either independently, or as a factor combined with aging, on disease phenotype, with relevance to the immune system and the CNS.